2003
DOI: 10.1046/j.1365-2133.2003.05329.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality trends of scabies in a young adult population: a 20-year follow-up

Abstract: Scabies in a young adult population is more frequent in the cooler months of the year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 5 publications
9
42
3
Order By: Relevance
“…Although we did not observe a significant seasonality trend in the incidence of scabies, seasonality trends for scabies infestations have been reported in a large population study of the Israeli Army (specifically, this study reported a higher incidence in winter than in summer) [20]. Many studies, in fact, have reported high incidences of scabies infestations during the cool weather of the fall and winter seasons [1, 25, 26].…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Although we did not observe a significant seasonality trend in the incidence of scabies, seasonality trends for scabies infestations have been reported in a large population study of the Israeli Army (specifically, this study reported a higher incidence in winter than in summer) [20]. Many studies, in fact, have reported high incidences of scabies infestations during the cool weather of the fall and winter seasons [1, 25, 26].…”
Section: Discussioncontrasting
confidence: 51%
“…In contrast, the mites have better survival and higher fertility rates in cool weather [4, 24], with the mite eggs being capable of remaining viable off of a host for up to 10 days at low temperatures [3]. Long-term observations from Scotland and Israel have demonstrated that the incidence of scabies in those countries was higher during cooler seasons, indicating that the increased person-to-person contact and overcrowding that occur in colder weather facilitate the spread of scabies [3, 20]. Consistent with these studies, our study also demonstrated a negative correlation between temperature and the rate of scabies infestations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And the West Bank, Palestinian Territories [19]. Similarly to [22][23][24][25]. Scabies was more prevalent in winter.…”
Section: Discussionmentioning
confidence: 99%